Coronavirus Disease-19 and Liver Injury - Siregar, Gontar Alamsyah; Siregar, Ginanda Putra; Darmadi, Darmadi; Ruslie, Riska Habriel (Open Access Macedonian Journal of Medical Sciences, 2020)
Coronavirus Disease (COVID)-19 is a pandemic since March 11, 2020. The total case is more than a half million worldwide. Liver injury is quite common in COVID-19 patients. Direct viral infection is possible due to the presence of angiotensin converting enzyme 2 in cholangiocytes and hepatocytes. Other proposed mechanisms are virus-induced cytopathic effects, inflammation process, hypoxia and shock, increased apoptotic activity, increased positive end expiratory effect, and drug-induced. The manifestation of liver injury is mild and transient with elevated liver enzymes, bilirubin, and gamma-glutamyl transferase levels. Deterioration of liver function can occur in subjects with COVID-19 and underlying liver injury. The management is principally supportive. Hepatoprotective drugs may be administered in severe cases.